Komponen Kebutuhan Hidup Dalam Regulasi Upah Minimum Perspektif Maqasid Al-Shariah - Adin Fadilah (IAIN Ponorogo, 2016)
Abstract: The provisions of minimum wage in Indonesia have been changing four times in the last few decades in line with the changes in the components of life needs referred. In fact, there are many life needs that previously were considered as trivial but they have now become important and should be referred to in setting the minimum wage. In Islam there are five sectors of human needs as established in the discourse of maqasid al-sharī'ah. Each sector is ranked into three levels, namely ḍarūrīyah, ḥajīyah, and taḥsīnīyah. This study examines how the components of life needs have been referred by the regulation of the minimum wage from the viewpoint of maqasid al-sharī'ah. This study came to the conclusion that the development of life needs used as guidelines in determining minimum wage levels has met the demands of life needs as intended by maqasid al-sharī’ah. Most of the components of decent living (KHL) occupy levels of ḍarūrīyah and ḥajīyah, and very few are classified as taḥsīnīyah. The enhancement of quantity and quality of the components proven the attention to the level of life needs sequentially from ḍarūrīyah level, the ḥajīyah, then the taḥsīnīyah level. These changes indicate the change of law in accordance with the demands of the circumstances.Abstrak: Komponen kebutuhan hidup yang dijadikan acuan dalam penetapan upah minimum di Indonesia telah mengalami perubahan sebanyak 4 kali. Perubahan ini terjadi karena menyesuaikan perkembangan kebutuhan dahulu dianggap sepele namun kini menjadi penting. Dalam Islam ada 5 unsur pokok kebutuhan manusia yang harus dipenuhi atau yang dikenal dengan istilah maqasid al-sharī’ah. Kelima unsur pokok maqasid al-sharī’ah ini terbagi mejadi 3 kategori yakni ḍarūrīyah, ḥajīyah, dan taḥsīnīyah. Penelitian ini mengkaji bagaimana komponen kebutuhan hidup dalam regulasi upah minimum perspektif maqasid al-sharī’ah. Penelitian ini memberi kesimpulan bahwa perkembangan kebutuhan hidup yang dijadikan pedoman dalam penentuan upah minimum telah memperhatikan tingkatan kebutuhan hidup. Sebagian besar komponen KHL ada pada wilayah ḍarūrīyah dan ḥajīyah, sedikit sekali yang tergolong taḥsīnīyah. Penambahan kuota komponen serta peningkatan kualitas komponen menjadi bukti bahwa adanya perhatian terhadap tingkatan kebutuhan dimulai dari yang ḍarūrīyah dulu baru kemudian yang ḥajīyah baru disusul yang taḥsīnīyah. Perubahan ini menunjukkan adanya perubahan hukum sesuai dengan perkembangan situasi.